2015
DOI: 10.1007/s11430-015-5134-2
|View full text |Cite
|
Sign up to set email alerts
|

Biostratigraphy constraining strontium isotopic stratigraphy and its application on the Lopingian (Late Permian)

Abstract: The Lopingian is one of the fastest rising periods of seawater strontium isotopic ratios ( 87 Sr/ 86 Sr) in earth history, and its mechanisms and increasing rates of the 87 Sr/ 86 Sr evolution were still disputed widely. These disputations among researchers were caused mainly by timeframe selection (sections' thickness or data of radiometric ages), and different stratigraphic boundaries and un-upmost dated ages. This paper examined published 87 Sr/ 86 Sr data of the Lopingian, and projected them on timescales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The Sr-isotope ratio decreased gradually from 0.708235 to 0.707026 from the Middle Permian to Early Permian in the study area, following the Sr-isotope evolution curve elsewhere that also gradually decreased during this period (Veizer et al, 1999;McArthur et al, 2001McArthur et al, , 2012. The Srisotope data in the middle stage of the Late Permian gradually increased from 0.707026 to 0.707255 in the study area, agreeing with 87 Sr/ 86 Sr values elsewhere that also tended to increase steadily during this period (Veizer et al, 1999;McArthur et al, 2001McArthur et al, , 2012, with 87 Sr/ 86 Sr values being linearly correlated with time (Veizer et al, 1999;Williamson et al, 2012;Liu et al, 2013;Ye et al, 2015). The Sr-isotope ratio increased sharply from 0.707255 to 0.707728 at the end of the Late Permian and at the turn of the PTB, just as the curve determined elsewhere (Veizer et al, 1999;McArthur et al, 2001McArthur et al, , 2012Shen and Mei, 2010).…”
Section: Sr-isotope Evolution Curve and Its Global Comparisonsupporting
confidence: 71%
See 1 more Smart Citation
“…The Sr-isotope ratio decreased gradually from 0.708235 to 0.707026 from the Middle Permian to Early Permian in the study area, following the Sr-isotope evolution curve elsewhere that also gradually decreased during this period (Veizer et al, 1999;McArthur et al, 2001McArthur et al, , 2012. The Srisotope data in the middle stage of the Late Permian gradually increased from 0.707026 to 0.707255 in the study area, agreeing with 87 Sr/ 86 Sr values elsewhere that also tended to increase steadily during this period (Veizer et al, 1999;McArthur et al, 2001McArthur et al, , 2012, with 87 Sr/ 86 Sr values being linearly correlated with time (Veizer et al, 1999;Williamson et al, 2012;Liu et al, 2013;Ye et al, 2015). The Sr-isotope ratio increased sharply from 0.707255 to 0.707728 at the end of the Late Permian and at the turn of the PTB, just as the curve determined elsewhere (Veizer et al, 1999;McArthur et al, 2001McArthur et al, , 2012Shen and Mei, 2010).…”
Section: Sr-isotope Evolution Curve and Its Global Comparisonsupporting
confidence: 71%
“…The composition and evolution of the Sr isotopes of marine sediments (carbonates, sulfates, phosphates, etc. ), which stand as proxy for the original seawater, are not only important means for the study of major global geological events (Derry and France-Lanord, 1996;Goddé ris and Veizer, 2000;Huang et al, 2008;Song et al, 2015;Wierzbowski et al, 2017) and stratigraphic correlation (Huang and Zhou, 1997;Veizer et al, 1997;McArthur et al, 2001McArthur et al, , 2012Huang et al, 2002aHuang et al, , 2008Huang et al, , 2011Liu et al, 2013;Mutterlose et al, 2014), but also are one of the most effective tools for determining the age of marine sediments, and there are numerous successful age determination examples (Hess et al, 1989;McArthur et al, 1994McArthur et al, , 2001Dingle et al, 1997;Denison et al, 1998;Walter et al, 2000;Melezhik et al, 2001;Gleason et al, 2002;Ray et al, 2003;Huang et al, 2005b;Liu et al, 2013;Ye et al, 2015). At present, global Sr-isotope composition age databases (Howarth and McArthur, 1997;Veizer et al, 1999;McArthur et al, 2001) have been established internationally.…”
Section: Introductionmentioning
confidence: 99%
“…Well‐preserved authigenic micrite and conodont apatite are recommended as the best material for global 87 Sr/ 86 Sr correlation because of its local ambiance‐irrelative nature (Korte & Ullmann, 2016; Veizer et al, 1997). However, 87 Sr/ 86 Sr of marine carbonates could be also partially affected by local provenance and diagenesis (Diener et al, 1996; Tackett et al, 2014), although globally correlatable 87 Sr/ 86 Sr measurement on a marine‐water‐balanced authigenic carbonate could be analyzed after physical–chemical pretreatment (NH 4 Cl‐NH 3 , and NH 4 Ac‐HAc buffer) (Wang et al, 2011; Ye et al, 2015). Any recorded environmental information of a sedimentary sequence includes the global impacts and the local depositional fingerprint (Brennan et al, 2016; Wang et al, 2011; Ye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 7 million years prior to the P‐Tr extinction, a major biotic crisis, associated with global sea‐level fall, oceanic anoxia, and the volatile Emeishan flood basalt (EFB) eruption are well recorded in the Guadalupian–Lopingian (G‐L) (middle‐Late Permian) transition, and they are also marked by abnormal geochemical imprints (Chen, George, & Yang, 2009; Chen et al, 2019; Huang et al, 2019, 2019; Jin, 1993; Jin et al, 2006; Jin, Zhang, & Shang, 1994; Kaiho et al, 2005; Shen et al, 2018; Stanley & Yang, 1994; Wang, Cao, & Wang, 2004; Wignall et al, 2009, 2009; Xu, Chung, Shao, & He, 2010; Zhou et al, 2002). Although controversies remain on the pattern and cause of biotic mass extinction near the G‐L boundary (GLB) (Lai et al, 2008; Liu et al, 2013; Shen et al, 2018; Shen & Shi, 2002; Ye et al, 2015), some extreme environmental events are well revealed from the GSSP Penglaitan and Auxiliary Stratotype Section and Point (ASSP) at Tieqiao of Laibin area, including a loss of shallow habitats due to global regression (Chen et al, 2009; Hallam & Wignall, 1997; Wang et al, 2004; Wignall, Sun, et al, 2009; Wignall, Vėdrine, et al, 2009), the EFB eruption (Bagherpour et al, 2018; Courtillot, Jaupart, Manighetti, Tapponnier, & Besse, 1999; Huang, Chen, Wignall, et al, 2019), explosive volcanism and cooling (Ali, Thompson, Song, & Wang, 2002), the Kamura Event (Isozaki, Kawahata, & Ota, 2007), oceanic anoxia (Isozaki, 1997; Kaiho et al, 2005; Zhang et al, 2015), and a catastrophic methane outburst with low atmospheric oxygen (Retallack et al, 2006).…”
Section: Introductionmentioning
confidence: 99%